ANALYTICAL (C4) LEARNING OUTCOMES IN IRE: IMPLEMENTING THE TTW MODEL BASED ON RTE - Dea Putry Apfrilia; Agus Pahrudin; Era Octafiona; Baharudin Baharudin (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
Islamic Religious Education (IRE) learning in Vocational High Schools (SMK) should not merely focus on the acquisition of religious knowledge, but also emphasize the development of higher-order thinking skills, particularly analytical thinking at the C4 cognitive level. However, learning outcomes in IRE at SMK SMTI Bandar Lampung remain relatively low, especially in tasks requiring analytical reasoning, largely due to conventional instructional practices that provide limited opportunities for active student engagement. This study aimed to examine the effectiveness of the Think Talk Write (TTW) learning model integrated with the Rotating Trio Exchange (RTE) strategy in improving students’ learning outcomes in IRE at the C4 cognitive level. A quantitative approach was employed using a quasi-experimental method with a post-test only control group design. The research sample consisted of two classes: an experimental class taught using the TTW model based on RTE and a control class receiving conventional instruction. Data were collected using a multiple-choice test designed to assess students’ analytical skills (C4). Data analysis involved normality testing, homogeneity testing, the Independent Samples t-test, and the Mann–Whitney test. The analysis results indicate that the data did not meet the assumptions of normality and homogeneity; however, a statistically significant difference in learning outcomes was found between the experimental and control groups (p < 0.05). These results demonstrate that the TTW–RTE model significantly improves students’ analytical thinking skills in IRE. Therefore, the TTW–RTE model can be considered an effective HOTS-oriented instructional alternative for improving analytical abilities among vocational high school students. ABSTRAK Pembelajaran Pendidikan Agama Islam (PAI) di Sekolah Menengah Kejuruan (SMK) idealnya tidak hanya berorientasi pada penguasaan materi keagamaan, tetapi juga pada pengembangan kemampuan berpikir tingkat tinggi, khususnya kemampuan menganalisis pada level kognitif C4. Namun, kenyataan di SMK SMTI Bandar Lampung menunjukkan bahwa hasil belajar PAI masih rendah, terutama pada soal-soal yang menuntut kemampuan analitis, akibat pembelajaran yang cenderung konvensional dan kurang melibatkan siswa secara aktif. Penelitian ini bertujuan untuk menganalisis efektivitas model pembelajaran Think Talk Write (TTW) yang dipadukan dengan strategi Rotating Trio Exchange (RTE) dalam meningkatkan hasil belajar PAI dalam ranah kognitif C4. Penelitian menggunakan pendekatan kuantitatif dengan desain quasi eksperimen tipe post-test only control group design. Sampel penelitian terdiri atas dua kelas, yakni kelas eksperimen menerapkan model TTW berbasis RTE sedangkan kelas kontrol menerapkan pembelajaran konvensional. Instrumen pengumpulan data berupa tes pilihan ganda yang dirancang untuk mengukur kemampuan analisis siswa. Data dianalisis menggunakan uji normalitas, uji homogenitas, uji Independent Sample t-Test, serta uji Mann–Whitney. Hasil analisis menunjukkan bahwa data penelitian tidak memenuhi asumsi normalitas dan homogenitas, namun terdapat perbedaan hasil belajar yang signifikan antara kelompok eksperimen dan kelompok kontrol dengan nilai signifikansi < 0,05. Temuan ini menunjukkan bahwa penerapan model TTW berbasis RTE secara signifikan meningkatkan keahlian analitis siswa pada pembelajaran PAI. Dengan demikian, dapat disimpulkan bahwa model TTW berbasis RTE efektif digunakan sebagai alternatif strategi pembelajaran PAI berbasis HOTS, khususnya guna meningkatkan kemampuan berpikir analitis siswa SMK.